How globalization affects the teaching of English: studying culture through texts - Gerbig, Andrea; Müller-Wood, Anja (Mellen, 2006)
The cultural nexus: setting the tone for interdisciplinarity -- Resources and implementations -- Applications
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Globalisierung; Englischunterricht